1998
DOI: 10.1159/000030024
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-Dependent Modulation of Interaction between Human Alpha-Fetoprotein and Its Monoclonal Antibodies

Abstract: The effect of lentil lectin (LCA) on the binding of mouse monoclonal antibody (MoAb) against human α-fetoprotein (AFP) to LCA-nonreactive AFP-L1 and LCA-reactive AFP-L3 was studied on a panel of 30 MoAbs provided by the TD-2 Workshop of ISOBM for epitope mapping. LCA inhibited the binding of MoAbs 93 and 98 to AFP-L3 but not to AFP-L1, indicating that there was a competition between the MoAbs and LCA for the AFP sugar chain. With MoAbs 100, 109, 118, and 120, LCA rather increased the binding to AFP-L3 over tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…Yakimenko et al [16] in Dr. Abelev's laboratory confirmed the presence of 6 major epitope clusters and identified several minor epitopes. These results were almost identical to that found by Dr. Nustad et al [17] and Kamakura [18] found that one of the epitopes did apparently contain carbohydrate in their studies. Dr. Karamova et al [19] …”
supporting
confidence: 90%
“…Yakimenko et al [16] in Dr. Abelev's laboratory confirmed the presence of 6 major epitope clusters and identified several minor epitopes. These results were almost identical to that found by Dr. Nustad et al [17] and Kamakura [18] found that one of the epitopes did apparently contain carbohydrate in their studies. Dr. Karamova et al [19] …”
supporting
confidence: 90%
“…Initially, some of the different forms have been attributed to carbohydrate microheterogeneity and variations in isoelectric points (Smith and Kelleher, 1980;Crandall, 1981). Some AFP isoforms were lectin glycoforms that were detected and isolated by isoelectric focusing, electrophoresis, and chromate-graphic methods (Breborowicz, 1988;Taketa et al, 1998). Other isoforms were detected following high-pressure liquid chromatography (HPLC), and lectin, heavy metal, and hydrophobic solid phase separation methods.…”
Section: Structural Variantsmentioning
confidence: 99%
“…Tetrameric ConA efficiently inactivates viral infectivity (8) and may interfere with the interaction between Fab-pp and the epitope because of its spatial bulkiness when it reacts with the glycomoiety near the target epitope (20). Figure 2 ognized by anti-gH neutralizing MAbs were protein portions or at least not glycomoieties of gH that interact with ConA.…”
Section: Varicella-zoster Virus (Vzv) Glycoprotein H (Gh)mentioning
confidence: 99%